Pengujian Aplikasi Sistem Informasi Akademik Berbasis Web Menggunakan Metode Black Box Testing Equivalence Partitioning - Ayu Sri Wulandari; Ahmad Saepudin; Meitasya Putri Kinanti; Ziki Sudesi; Aries Saifudin; Yulianti Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
To check the specifications of a software, it is necessary to have a test and validation is something that is needed when testing the software. The inappropriateness of the data input process is caused by the validation process that is not optimal, one of the consequences is that the data addition process fails. Therefore, the application can cause harm to the user. Therefore, improving the quality of accurate validation is very necessary. When the testing process finds an error that was not previously known, then the test can be said to be a good test. One of them is the Black Box testing method, in this test the author chose the iEquivalence Partition testing method. Equivalence Partition is a technique used to reduce the number of test cases that exist at the time of testing. Based on the tests that have been carried out, the authors conclude that this software can be used properly, after repairing the errors that have been found. However, this test is not perfect, because it is only done by using a few samples. From the results of this test, it is expected that the application can be used according to user needs.